Ferromagnetism of three-dimensional graphene framework. Issue 113 (29th October 2015) - Qin, Sai; Sun, Pingping; Di, Qitao; Zhou, Shuang; Yang, Caiping; Xu, Qingyu
Abstract : A three-dimensional graphene framework (3DGF) was synthesized via hydrothermal growth of graphene oxide (GO) suspension. Abstract : A three-dimensional graphene framework (3DGF) was synthesized via hydrothermal growth of graphene oxide (GO) suspension. The structure of 3DGF was characterized by scanning electron microscope, Raman spectroscopy and X-ray photoelectron spectroscopy. The reduction of GO with increased defect density has been confirmed, promoting the formation of 3D pore structure. The magnetic properties of 3DGF were investigated experimentally. Pure diamagnetism was observed in GO, while weak ferromagnetism was observed in 3DGF with saturated ferromagnetic magnetization of 0.005 emu g −1 at 300 K. The observed ferromagnetism has been attributed to the presence of increased concentration of sp 3 -type hydroxyl groups attached on the basal plane at the interconnected 3D porous network structure of 3DGF.